Consumption of Coprinus comatus polysaccharide extract causes recovery of alcoholic liver damage in rats. (August 2014) - Ozalp, Fatma Ozgul; Canbek, Mediha; Yamac, Mustafa; Kanbak, Gungor; Van Griensven, Leo J. L. D.; Uyanoglu, Mustafa; Senturk, Hakan; Kartkaya, Kazım; Oglakci, Aysegul
Abstract Context: Excess use of alcohol is known to be associated with liver diseases such as fatty liver, alcoholic hepatitis, and cirrhosis. Various practices may be applied to prevent or treat the damage caused by chronic alcoholism. Coprinus comatus (O.F. Müll.) Pers. (Agaricaceae) is a macrofungus that has been reported to aid the recovery of murine livers damaged by benzopyrene. Objective: In this study, the possible therapeutic effects of three different doses (50, 100, and 150 mg/kg) of C. comatus polysaccharide (PS) extract were studied in rats subjected to an alcoholic diet. The histological and biochemical results were compared between the control and experimental groups. Materials and methods: Modified Lieber–Decarli's calorie-adjusted liquid alcohol diet was given orally for 60 d. In addition to histopathology, alanine transaminase (ALT), aspartate transaminase (AST), mitochondrial membrane integrity, total cytochrome-c oxidase activity (TotalStCox), total mitochondrial cytochrome-c oxidase activity (TotalMtStCox), and caspase-3 values were used as liver parameters, and liver sections from all experimental groups were examined by electron microscopy. Results: Using histopathological assessment, it was observed that there was a decline in liver hepatocyte vacuolization in the treatment group fed 50 mg PS/kg. The TotalStCox and TotalMtStCox values of this group differed from the EtOH control group (p < 0.05). Discussion and conclusion: Daily administration of 50 mg/kg of C. comatus PS extract considerably reduced the negative effects of alcohol on liver structure and function.